Changes in Trauma‐Related Emotions Following Treatment With Dialectical Behavior Therapy for Posttraumatic Stress Disorder After Childhood Abuse. Issue 5 (2nd September 2019) - Görg, Nora; Böhnke, Jan R.; Priebe, Kathlen; Rausch, Sophie; Wekenmann, Stefanie; Ludäscher, Petra; Bohus, Martin; Kleindienst, Nikolaus
Abstract: Dialectical behavior therapy for posttraumatic stress disorder (DBT‐PTSD) is a trauma‐focused therapy shown to reduce core PTSD symptoms, such as intrusions, hyperarousal, and avoidance. Preliminary data indicate effects on elevated trauma‐related emotions (e.g., guilt and shame) and possibly radical acceptance of the traumatic event. However, it is unclear if improvements in these variables are significant after controlling for changes in core PTSD symptoms and to what extent nonclinical levels are obtained. In the current study, 42 individuals who met criteria for PTSD after childhood abuse and were participating in a 3‐month residential DBT‐PTSD program were evaluated at the start of the exposure phase of DBT‐PTSD and the end of treatment; a nonclinical sample with a history of childhood abuse was the reference group. Multivariate analyses of variance and multivariate analyses of covariance controlling for change in core PTSD symptoms were used to evaluate changes in several elevated trauma‐related emotions (fear, anger, guilt, shame, disgust, sadness, and helplessness) and in radical acceptance. In a repeated measures multivariate analyses of variance, both elevated trauma‐related emotions and radical acceptance significantly improved during DBT‐PTSD, λ = 0.34, p < .001; η 2 = .56; t (40) = −5.66, p < .001, SMD = 0.88, even after controlling for changes in PTSD symptoms, λ = 0.35, p < .001, η 2 = .65; Λ = 0.86, p = .018, η 2 = .14, respectively. Posttreatment, 31.0% (for acceptance) to 76.2% (for guilt) of participants showed nonclinical levels of the investigated outcomes, suggesting that both trauma‐related emotions and radical acceptance changed after the 3‐month residential DBT‐PTSD program. Resumen: Spanish Abstracts by Asociación Chilena de Estrés Traumático (ACET) Los Cambios en las Emociones Relacionadas al Trauma posterior al Tratamiento con Terapia Dialéctica Conductual para el Trastorno de Estrés Traumático después de Abuso Infantil EMOCION RELACIONADA AL TRAUMA Y TERAPIA DIALECTICA CONDUCTUAL La terapia dialéctica conductual para el trastorno de estrés traumático (TDC‐TEPT) es una terapia centrada en el trauma que ha mostrado una reducción de los síntomas centrales del TEPT, tales como intrusiones, hiperactivación, y evitación. Resultados preliminares indican efectos sobre elevadas emociones relacionadas con el trauma (por ej., culpa y vergüenza) y la aceptación posiblemente radical del evento traumático. Sin embargo, no es claro si las mejoras en estas variables son significativas luego de controlar los cambios en los síntomas centrales del TEPT y en qué medida se obtienen niveles no clínicos. En el presente estudio, 42 individuos que cumplieron con los criterios para el TEPT luego de un abuso infantil y que participaron en un programa residencial de la TDC‐TEPT por 3 meses fueron evaluados al principio de su etapa de exposición a la TDC‐TEPT y al final del tratamiento; una muestra no clínica con una historia de abuso infantil fue el grupo de referencia. Análisis multivariados de varianza y análisis multivariados de covarianza controlando los cambios en los síntomas centrales del TEPT fueron usados para evaluar los cambios en diferentes emociones relacionadas al trauma elevadas (temor, rabia, culpa, vergüenza, disgusto, tristeza, y desesperanza) y una aceptación radical. En los análisis multivariados de la varianza de medidas repetidas, las elevadas emociones relacionadas al trauma y la aceptación radical mejoraron significativamente durante la TDC‐TEPT, λ = 0.34, p < .001; η 2 = .56; t (40) = ‐5.66, p < .001, SMD = 0.88, incluso luego de controlar por los cambios en los síntomas del TEPT, λ = 0.35, p < .001, η 2 = .65; Λ = 0.86, p = .018, η 2 = .14, respectivamente. Al término del tratamiento, 31.0% (para aceptación) al 76.2% (para culpa) de los participantes mostraron niveles no clínicos de los resultados investigados, sugiriendo que tanto las emociones relacionadas con el trauma como la aceptación radical, cambió luego del programa residencial de la TDC‐TEPT por 3 meses. 抽象: Traditional and Simplified Chinese Abstracts by the Asian Society for Traumatic Stress Studies (AsianSTSS) 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 Changes in Trauma‐related Emotions Following Treatment with Dialectical Behavior Therapy for Posttraumatic Stress Disorder after Childhood Abuse Traditional Chinese 標題: 童年時經歷虐待而患創傷後壓力症, 接受辯證行為治療後, 創傷相關情緒的變化 撮要: 為創傷後壓力症而設的辯證行為治療(DBT‐PTSD), 乃聚焦創傷的療法, 證實可減輕PTSD的核心症狀, 如侵擾、過度激發、迴避。初步的研究數據反映, 此療法對提升了的創傷相關情緒 (如內疚、羞恥) 及有可能激進地接受創傷事件有所效應。然而, 我們仍不清楚這些變量的改善, 在對PTSD的核心症狀改變作對照後是否仍為顯著, 以及效應在非臨床水平的可見程度有多大。研究樣本為42名童年時經歷虐待並符合患PTSD準則的人士。他們參與為期3個月的DBT‐PTSD住院治療計劃, 在暴露階段開始前及完成治療後接受評估。我們採用一份童年時經歷虐待的非臨床樣本作為參考組。我們對變異量和協方差進行多變量分析, 並以PTSD的核心症狀改變作對照, 以評估幾種提升了的創傷相關情緒的變化 (恐懼、憤怒、內疚、羞恥、厭惡、悲傷、無助), 及激進的接受的變化。重複進行的變異量多變量分析顯示, 樣本接受DBT‐PTSD期間, 提升了的創傷相關情緒及激進的接受均有顯著改善(λ = 0.34, p < .001; η 2 = .56; t(40) = ‐5.66, p < .001, SMD = 0.88);即使對PTSD的症狀改變作對照後, 依然如是(λ = 0.35, p < .001, η 2 = .65; Λ = 0.86, p = .018, η 2 = .14)。完成治療後, 31.0%的樣本(在接受方面) 至 76.2%的樣本(在內疚方面)呈現非臨床水平的受檢視效應, 反映樣本的創傷相關情緒和激進的接受, 在完成為期3個月的DBT‐PTSD住院治療計劃後, 有所改變。 Simplified Chinese 标题: 童年时经历虐待而患创伤后压力症, 接受辩证行为治疗后, 创伤相关情绪的变化 撮要: 为创伤后压力症而设的辩证行为治疗(DBT‐PTSD), 乃聚焦创伤的疗法, 证实可减轻PTSD的核心症状, 如侵扰、过度激发、回避。初步的研究数据反映, 此疗法对提升了的创伤相关情绪 (如内疚、羞耻) 及有可能激进地接受创伤事件有所效应。然而, 我们仍不清楚这些变量的改善, 在对PTSD的核心症状改变作对照后是否仍为显著, 以及效应在非临床水平的可见程度有多大。研究样本为42名童年时经历虐待并符合患PTSD准则的人士。他们参与为期3个月的DBT‐PTSD住院治疗计划, 在暴露阶段开始前及完成治疗后接受评估。我们采用一份童年时经历虐待的非临床样本作为参考组。我们对变异量和协方差进行多变量分析, 并以PTSD的核心症状改变作对照, 以评估几种提升了的创伤相关情绪的变化 (恐惧、愤怒、内疚、羞耻、厌恶、悲伤、无助), 及激进的接受的变化。重复进行的变异量多变量分析显示, 样本接受DBT‐PTSD期间, 提升了的创伤相关情绪及激进的接受均有显著改善(λ = 0.34, p < .001; η 2 = .56; t(40) = ‐5.66, p < .001, SMD = 0.88);即使对PTSD的症状改变作对照后, 依然如是(λ = 0.35, p < .001, η 2 = .65; Λ = 0.86, p = .018, η 2 = .14)。完成治疗后, 31.0%的样本(在接受方面) 至 76.2%的样本(在内疚方面)呈现非临床水平的受检视效应, 反映样本的创伤相关情绪和激进的接受, 在完成为期3个月的DBT‐PTSD住院治疗计划后, 有所改变。